Sensivitas Etis Mahasiswa - Tony Wijaya (JURNAL ILMU MANAJEMEN, 2016)
This study generally aims to examine differences in the ethical sensitivity of students by gender and level of the semester. The data collection is conducted by selecting economic and business students in Yogyakarta. Data analysis method used is Independent Samples T-Test. The study found that there are differences in ethical sensitivity significantly between male and female students. Ethical sensitivity level on female students better than the ethical sensitivity of the male students. There are differences in ethical sensitivity significantly between the senior students and the junior students. Ethical sensitivity levels at the senior students better than ethical sensitivity at the junior students.